2018
DOI: 10.1002/rcm.8127
|View full text |Cite
|
Sign up to set email alerts
|

Solvent composition dependent signal reduction of molecular ions generated from aromatic compounds in (+) atmospheric pressure photoionization mass spectrometry

Abstract: A solvent composition dependent signal reduction mechanism was suggested and evaluated for the (+)-APPI-MS analysis of polyaromatic hydrocarbons (PAHs) generating mainly molecular ions. Overall, the evidence provided in this work suggests that reactions between solvent cluster(s) and toluene molecular ions are responsible for the observed reductions in signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…44 Previous studies showed that chemical reactions such as charge transfer and/or proton transfer between solvent and analyte are important for APPI mechanism. [45][46][47] Therefore, there is a common element shared by PSCI, atmospheric pressure chemical ionization, and APPI mechanisms, and that can explain the improved ionization efficiency with chlorobenzene for both APPI and PSCI. It is notable that the data presented in Figure 4 show that the PSCI sensitivity does not strictly correlate with the dielectric constants.…”
Section: Resultsmentioning
confidence: 99%
“…44 Previous studies showed that chemical reactions such as charge transfer and/or proton transfer between solvent and analyte are important for APPI mechanism. [45][46][47] Therefore, there is a common element shared by PSCI, atmospheric pressure chemical ionization, and APPI mechanisms, and that can explain the improved ionization efficiency with chlorobenzene for both APPI and PSCI. It is notable that the data presented in Figure 4 show that the PSCI sensitivity does not strictly correlate with the dielectric constants.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the signal intensities were observed to reduce by different extents for the three catechol isomers as methanol was introduced into the toluene, which is in good agreement with our previous study that showed a reduction in signal intensity when methanol was used as a co‐solvent with toluene in (+) APPI …”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26] Many ionization techniques are used in LC/MS, among which atmospheric pressure photoionization (APPI), atmospheric pressure chemical ionization (APCI), and electrospray ionization (ESI) are most the common and popular. [27][28][29][30][31][32][33][34][35][36] Despite their identical molecular formulas, isomers exhibit different physical and chemical properties; however, their similarities make it difficult to explain some of their experimentally observed properties. For this reason, many studies aimed at understanding the APPI ionization mechanism have been conducted in order to better use this technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the revealed mechanisms behind the H-abstraction reactions occurring on PI source may provide illuminating insights into the H-abstraction fundamentals on EI source. On PI source, the hydrogen source for H-abstraction reactions is protic solvents used for injection, such as toluene, 29 water, 32 methanol, 33 ethanol and hexane. 28 Whereas aprotic solvents such as tetrachloromethane and aprotic gases including N2, O2 and CO2 could compete with analytes to abstract hydrogen atoms, thus impair the MS signal intensities of [M+H] + .…”
Section: Rh + [M] •+ → R • + [M+h] + (1)mentioning
confidence: 99%